Autologous transfusion in a patient with life threatening traumatic haemothorax: Case Report. (Bangladesh Journal of Medical Science, 2013)
Penetrating thoracic injuries frequently presents a challenge to the clinicians. The situation may become more deleterious owing to the unavailability of adequate blood of required group. We discuss the acute management of a patient with life threatening traumatic haemothorax following penetrating thoracic injury. In this patient, autologous transfusion of patient blood collected in chest drain was performed during intraoperative period using an indigenous technique with successful outcome. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14146 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 76-79